2011
DOI: 10.1080/19338244.2011.564228
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Description of an Outbreak of Dermatitis Related to Dimethylfumarate, France, 2008

Abstract: Following similar events in other European countries, some cases of dermatitis related to contact with China-imported furniture possibly treated with dimethyl(E)-butenedioate (dimethylfumarate [DMF]) were reported to the French institute for public health surveillance at the beginning of September 2008. An active multisource case collection was conducted in order to provide an epidemiological description of this outbreak. Results of this investigation show that, in France, mainly during the 4th quarter of 2008… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Historically, poison control centres in both the United States and Europe have demonstrated their capacity to alert public health, 15 law enforcement 23 and drug and consumer product agencies 17 when public health action is required. Surveillance of poison control centre information has been used to detect and monitor the emergence of trends and real-time incidents involving drug and substance abuse, 24,25 food-borne illness, 26 mass poisoning, 27 food/medication contamination, 28,29 adverse drug reactions 19,30 and injuries from commercial and consumer products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, poison control centres in both the United States and Europe have demonstrated their capacity to alert public health, 15 law enforcement 23 and drug and consumer product agencies 17 when public health action is required. Surveillance of poison control centre information has been used to detect and monitor the emergence of trends and real-time incidents involving drug and substance abuse, 24,25 food-borne illness, 26 mass poisoning, 27 food/medication contamination, 28,29 adverse drug reactions 19,30 and injuries from commercial and consumer products.…”
Section: Discussionmentioning
confidence: 99%
“…Poison control centres have been used to field exposure-and information-related calls following large-scale natural disasters, 15,16 consumer product concerns, 17 adverse drug effects, 18,19 food-borne outbreaks 20 and to quell public anxiety about the H1N1 virus. 21 Largely unrecognized and untapped, however, particularly in Canada, is their potential as a source of information to identify and monitor emerging public health issues.…”
Section: Introductionmentioning
confidence: 99%
“…An initial report published in 2009 showed that, in France, mainly during the fourth quarter of 2008, a large number of people presented dermatological symptoms, at least plausible ones, due to contact with DMFu‐treated consumer products . The products involved were mostly shoes and sofas (94% of cases) …”
Section: Methodsmentioning
confidence: 99%
“…Compared to the first period of data collection, causality assessment was improved by using a two‐step method. In the first step, the causal relationship between symptoms and the suspected article was evaluated using the French method for unexpected or toxic drug reaction assessment .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation